COVID-19 Outbreak in Mauritius: Transmission through Importation, International Trade and Implications for Future Pandemics - Robinson, Jared; Leclézio, Alexandra; Banerjee, Indrajit (Current Practice in Medical Science Vol. 8, 2022)
Mauritius recorded its first three cases of SARS-CoV-2 on March 18, 2020, all of which had an international travel history. On March 23, 2020 a six-week complete national lockdown of the island nation which has since been praised by the WHO commenced. A total of 335 cases were detected until June 02, 2020 with a total of 10 deaths being recorded. The island nation has since been a COVID “safe” country, with no known community cases circulating within the general populous. The enhanced indomitability of the virus to survive on inanimate objects is believed to have caused the now current second wave of SARS-CoV-2 infections in Mauritius. Mauritius lost its COVID “safe” status after a cluster of SARS-CoV-2 cases were detected in a fruit importation enterprise. The virus is believed to have been imported on stock from another country, consequently infecting employees and causing an outbreak with multiple secondary clusters. The cases are expected to continue rising as further contact tracing takes place. The current situation developing in Mauritius should be used as a global case study as Mauritius is an example of how a nation can be shifted from COVID “safe” (with no circulating active cases within the general populous) to a full scale second wave of infections due to the importation and subsequent transmission of the virus through its importation. It is critical to assess what measures can be put into place to prevent such importation of the virus from occurring.